Assessment of OMT-28, a synthetic analog of omega-3 epoxyeicosanoids, in patients with persistent atrial fibrillation: Rationale and design of the PROMISE-AF phase II study. (August 2020) - Berlin, Sarah; Goette, Andreas; Summo, Luciana; Lossie, Janine; Gebauer, Alexander; Al-Saady, Naab; Calo, Leonardo; Naccarelli, Gerald; Schunck, Wolf-Hagen; Fischer, Robert; Camm, A.John; Dobrev, Dobromir
Abstract: We designed a placebo controlled, double-blind, randomized, dose-finding phase II study on OMT-28 in the maintenance of sinus rhythm after electrical cardioversion (DCC) in patients with persistent atrial fibrillation (PROMISE-AF). OMT-28 is a first-in-class, synthetic analog of 17, 18-epoxyeicosatetetraenoic acid, a bioactive lipid mediator generated by cytochrome P450 enzymes from the omega-3 fatty acid eicosapentaenoic acid. OMT-28 improves Ca 2+ -handling and mitochondrial function in cardiomyocytes and reduces pro-inflammatory signaling. This unique mode of action may provide a novel approach to target key mechanism contributing to AF pathophysiology. In a recent phase I study, OMT-28 was safe and well tolerated and showed favorable pharmacokinetics. The PROMISE-AF study (NCT03906799) is designed to assess the efficacy (primary objective), safety, and population pharmacokinetics (secondary objectives) of three different doses of OMT-28, administered once daily, versus placebo until the end of the follow-up period. Recruitment started in March 2019 and the study will include a total of 120 patients. The primary efficacy endpoint is the AF burden (% time with any AF), evaluated over a 13-week treatment period after DCC. AF burden is calculated based on continuous ECG monitoring using an insertable cardiac monitor (ICM). The primary efficacy analysis will be conducted on the modified intention-to-treat (mITT) population, whereas the safety analysis will be done on the safety population. Although ICMs have been used in other interventional studies to assess arrhythmia, PROMISE-AF will be the first study to assess antiarrhythmic efficacy and safety of a novel rhythm-stabilizing drug after DCC by using ICMs.